2020
DOI: 10.1128/aac.00713-20
|View full text |Cite
|
Sign up to set email alerts
|

Ethionamide Population Pharmacokinetic Model and Target Attainment in Multidrug-Resistant Tuberculosis

Abstract: Ethionamide (ETA), an isonicotinic acid derivative, is part of multidrug-resistant tuberculosis (MDR-TB) regimen. The current guidelines deprioritized ETA due to potential less effectiveness compared to other agents. Our aim was to develop a population pharmacokinetic (PK) model and simulate ETA dosing regimens to assess target attainment. This study included subjects from four different sites, including both healthy volunteers and patients with MDR-TB. The TB centers included were two in the US and on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…This is consistent with the studies of Auclair et al and Thee et al, 10,15 who additionally reported significant BSV in plasma concentrations of ethionamide in children with DS‐TB as well as adult healthy volunteers. Similarly, in the study by Al‐Shaer et al, 27 no covariates included in the ethionamide pharmacokinetic model improved the fit or led to a decrease in BSV. FMO3 is the predominant liver enzyme that biotransforms ethionamide into ethionamide sulfoxide 8 .…”
Section: Discussionmentioning
confidence: 83%
“…This is consistent with the studies of Auclair et al and Thee et al, 10,15 who additionally reported significant BSV in plasma concentrations of ethionamide in children with DS‐TB as well as adult healthy volunteers. Similarly, in the study by Al‐Shaer et al, 27 no covariates included in the ethionamide pharmacokinetic model improved the fit or led to a decrease in BSV. FMO3 is the predominant liver enzyme that biotransforms ethionamide into ethionamide sulfoxide 8 .…”
Section: Discussionmentioning
confidence: 83%
“…To date, only noncompartmental analyses were conducted for PTO, and this study was the first to develop a population PK model of the drug. Meanwhile, population PK models for ETO have been developed from clinical trials of patients with tuberculosis (12)(13)(14). According to previous research, the oral bioavailability of PTO and ETO were 0.9 and 1.1, respectively (5,15).…”
Section: Discussionmentioning
confidence: 99%
“…The PTO fAUC ss was calculated using noncompartmental analysis of the simulation results by the ncappc package of R software (R Foundation for Statistical Computing, Vienna, Austria) (22). The free fraction was assumed to be 70% (12,23). The range of MIC values for M. tuberculosis was set at 0.8 to 8 mg/mL, as reported by Tan et al (10).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to observe delayed absorption, and to assess elimination, sampling at 2 and 6 hours post dose is suggested [3,141]. A fAUC/ MIC target of 10 has been proposed for 1.0-log kill, which has shown to be attained with daily dose of 750 mg and higher [65,143]. TDM of ethionamide could be useful in order to strive toward PK/PD targets, although patient tolerability often limits doses [143].…”
Section: Ethionamide and Prothionamidementioning
confidence: 99%